(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
NPAs in the Indian banking sector have become a major concern for theIndian economy. NPA has a direct impact on the profitability, liquidity andsolvency position of the bank. Higher NPA indicates inefficiency of the bankand lower NPA indicate better performance and management of funds. To improvethe efficiency and profitability of banks the NPA need to be reduced andcontrolled. This paper basically deals with the trends of NPA in bankingindustry, the factors that mainly contribute to NPA raising in the bankingindustry and also provides some suggestions how to overcome this burden of NPAon banking industry[1].